Dimensi Irasional Mendominasi Rasionalitas dalam Financial Behavior - Hanif Hanif (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of the research is to compile a new concept of financial behavior through field observation. The research method uses case studies with an interpretive paradigm to understand the social reality of financial behavior. Data was obtained from participant observation with unstructured interviews with informants. Data analysis uses an inductive approach, that is, the field data is narrated, then analyzed and abstracted. The findings of the research is the production of the concept of financial behavior from the context of research on four individual business people, who are in the position of company leaders. The research results describe two dimensions of financial behavior, the psychological dimension and the financial dimension. The psychological dimension consists of thirteen indicator elements, consisting of six positive statement items and seven negative statement indicators. While the financial dimension is broken down into seven indicators, consisting of five positive statements and two negative statements. The conclusion of the research is that financial decision-making by company leaders is not only based on economic analysis, but every decision involves their entire psychological condition. Even in certain conditions, irrationality dominates the aspect of rationality in business decision-making. Keywords: Case Studies, Financial Behavior, Inductive, Participant Observation